Urban Adolescents and Sexual Risk Taking - Štulhofer, Aleksandar (Array, 2001)
The paper analyzes socio-cultural and psychosocial factors affecting sexual activities and related risk-taking behaviors in Croatian high-school students. It attempts to determine the correlates of sexual activity, early sexual initiation, the number of sexual partners, and the use of contraceptives and condoms. Due to the gender-specific trajectories of sexual socialization and initiation, all the analyses were carried out separately for female and male students. The results point out gender-specific structure of adolescent sexual risk-taking, clustering of risk-taking activities, and the habitual character of sexual risk-taking. These findings should be instrumental for the development of a comprehensive school-based sex education curriculum that Croatia lacks.